KAJIAN PETA PERSAINGAN PASAR MODERN RETAIL BERBASIS WILAYAH DI LINGKUNGAN PINGGIRAN KOTA/PEDESAAN KOTA SEMARANG - Rara Ririn Budi Utaminingtyas; Inayah Inayah; Fatchun Hasyim; Khairul Saleh; M Nahar (Admisi dan Bisnis, 2017)
The objectives of this research is to find out and see the competition map among retailbusinesses, such as the modern market such as Alfamart franchise minimarket and other retailstores, with traditional markets. It is done because of the rapid development of modern shopsstart from the city center to suburban and even rural areas. The existence of modern stores thatprovide convenience to the public in the shopping needs and comfort while shopping encourageintense competition among modern franchise stores for market share of traditional markets. Towin the competition companies must make the consumers as loyal customers and loyal buyers.The method used in this research is assessing the strengths, weaknesses, opportunities andthreats (SWOT) analysis. Based on the results of SWOT analysis the company is expected to beable to define the strategy (corporate, business, function) to win the competition. The samples ofthis research were selected randomly. 50 Alfamart employees were selected as the internalsamples (the samples from within the company). 100 Alfamarts consumers / customers who haveshopped at lest once (1 times) have been selected as the external samples (samples from outsidethe company). The data data collecting method were questionnaires, interviews, andobservations. The data were analyzed with matrix method IFAS and EFAS. To determine theposition of the company, the coordinates of the customer side is the x-axis and y-axis = 0.14 =0.33 are in quadrant 1 (one) as well as from the employees of the coordinate axes x = 0 , 50 andthe axis y = 0.26 which is also located in quadrant 1 (one). It means that the company is in astrong position and also has strong opportunity. The strategy adopted is an aggressive strategyor growth strategies.